2014
DOI: 10.5657/fas.2014.0345
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Copper and Temperature on Antioxidant Enzymes in the Black Rockfish Sebastes schlegeli

Abstract: Copper has been widely used to control algae and pathogens in fish culture ponds. However, its toxic effects on fish depend not only on its concentration in the water but also on the water quality. A laboratory experiment was conducted to assess copper toxicity in the black rockfish Sebastes schlegeli using a panel of antioxidant enzymes, including glutathione (GSH), glutathione S-transferase (GST), glutathione peroxidase (GPx), glutathione reductase (GR) and superoxide dismutase (SOD), at different levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Supporting this comfort scope theory, TG levels decreased at lower temperatures. This also reveals similarities in the response to pollution stress (Al-Ghais, 2013) as well as other chemical aggressions (Min & Kang, 2014). Our results showed an increase in TG levels at higher temperatures, a result directly connected to the GSH levels.…”
Section: Biomarkerssupporting
confidence: 79%
“…Supporting this comfort scope theory, TG levels decreased at lower temperatures. This also reveals similarities in the response to pollution stress (Al-Ghais, 2013) as well as other chemical aggressions (Min & Kang, 2014). Our results showed an increase in TG levels at higher temperatures, a result directly connected to the GSH levels.…”
Section: Biomarkerssupporting
confidence: 79%
“…Under elevated temperatures, GPx expression levels in fishes may increase 42,43 or decrease. 14,44 Effects of temperature increase on cellular mechanisms are still poorly understood, especially those related to redox chemistry. 45,46 It is reported that elevated temperature results in enhanced oxygen consumption and ROS production.…”
mentioning
confidence: 99%
“…Despite its toxicity, copper sulphate is used for the control of mortality caused by external bacteria, external parasites, and fungus on finfish and finfish eggs in hatcheries [11]. In aquaculture practices, copper sulphate has also been widely used to control algae and other pathogens [12]. The use of copper sulphate in the control of algae and other parasites in water requires high concentrations which are recommended at 50 μg/L minimal dose [13].…”
mentioning
confidence: 99%